Network toxicology and molecular docking techniques to explore the mechanism of bisphenol A on obesity. - Lingjuan, Yang; Yu, Huang; Lei, Zhang (International Journal of Environmental Health Research, 2025)
The study investigates how bisphenol A (BPA) exposure may lead to obesity (OB) by identifying molecular mechanisms and suggests a new research approach for examining the health effects of chemical toxins. Researchers identified 237 potential targets associated with BPA exposure and OB using CTD, STITCH, DrugBank, GeneCards, and OMIM databases. Analysis with STRING and Cytoscape revealed 10 key targets, including INS, IL-6, AKT1, and PPARG. Enrichment analysis via the DAVID database indicated that these targets are primarily involved in PI3K-Akt and Insulin signaling pathways. These findings indicate that BPA may contribute to the occurrence and development of OB by influencing apoptosis, proliferation, inflammatory signaling, and insulin resistance. Molecular docking showed strong binding of BPA to INS, IL-6, AKT1, and PPARG, with molecular dynamics simulations revealing a stable complex of BPA and PPARG. This study offers insights into BPA's role in OB and supports efforts to prevent and treat OB diseases linked to exposure to BPA-containing plastic products and certain BPA-inundated environments.